2018
DOI: 10.1088/1758-5090/aa92a2
|View full text |Cite
|
Sign up to set email alerts
|

Facile and controllable electrochemical fabrication of cell-adhesive polypyrrole electrodes using pyrrole-RGD peptides

Abstract: Electrically conductive polymers, such as polypyrrole (PPy), have been widely used for the fabrication of various biosensors and tissue engineering scaffolds. For their biologically relevant applications, conductive biomaterials capable of intimate cellular interactions are highly desired. However, conventional methods to incorporate biomolecules into conductive polymers do not offer fine and easy control over the surface density of the biomolecules and/or their stability. We present a novel method to electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…During the process of oxidative polymerization of Ppy, the pendant methacrylate groups of GelMA formed a self-crosslinked network 4 , 56 , helping the formation of spherical GelMA-Ppy nanoparticles. It seems that Ppy does not provide cell-interactive moieties, and the self-crosslinked network of GelMA-Ppy improves the cytocompatibility of Ppy 43 , 57 . The incorporation of GelMA in GelMA-Ppy nanoparticles was bifunctional, keeping the nanoparticles conductive and promoting cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of oxidative polymerization of Ppy, the pendant methacrylate groups of GelMA formed a self-crosslinked network 4 , 56 , helping the formation of spherical GelMA-Ppy nanoparticles. It seems that Ppy does not provide cell-interactive moieties, and the self-crosslinked network of GelMA-Ppy improves the cytocompatibility of Ppy 43 , 57 . The incorporation of GelMA in GelMA-Ppy nanoparticles was bifunctional, keeping the nanoparticles conductive and promoting cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Higher than 9.7 µg/mL Ppy polymerized by oxidative doping has been considered harmful for cell viability/proliferation 42 . A recent in vitro study reported that polypeptide-conjugated Ppy-coated metal electrode displays excellent cytocompatibility 43 , 44 . Gelatin, a natural polymer, can be self-crosslinked into a monomolecular or network structure in dilute solutions 45 - 47 .…”
Section: Introductionmentioning
confidence: 99%
“…This poor cell growth is frequently observed when using PPY-based materials. 33 By comparison the PDA/PPY samples supported myoblast growth, with significantly more cells observed on PDA/PPY (50 mC) compared to the other PDA/PPY samples prepared with 100 mC, 200 mC, and 300 mC charges. Myoblast numbers on the thin PPY and all PDA/PPY substrates increased over 7 days of culture.…”
Section: 3mentioning
confidence: 94%
“…31,32 PPY biomaterials has been further modified by creating specific topographies, incorporating biomolecules (e.g., peptides, proteins, and polysaccharides), and modulating mechanical properties to improve their biological interactions. 28,31,33,34 Despite the unique benefits of CP-modified electrodes, their biocompatibility is often compromised by electrochemical functions (e.g. thick CP coatings can decrease the electrical impedance of electrodes but lead to poor cell attachment and growth).…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al reported an approach to electrochemically immobilize cell‐adhesive RGD ligands on PPy electrode surfaces. The surface peptide density was simply controlled by varying the electrodeposition time, and the hMSCs showed enhanced adhesion and proliferation on the PPy films with RGD peptides 56. This approach is useful for the fabrication of cell‐interactive scaffolds or bio‐electrodes.…”
Section: Electrochemical Modification On Cell Culture Surfacesmentioning
confidence: 99%